The effect of nerve stimulation on the axonal transport of noradrenaline and dopamine-β-hydroxylase - Keen, P. (1974)
1 A method for stimulating the lumbar sympathetic outflow from the spinal cord of the rat is described which does not require artificial respiration of the animal. 2 In some, but not all experiments continuous stimulation at 2 Hz or intermittently at 10 Hz accelerated the rate at which noradrenaline and dopamine-β-hydroxylase accumulated central to a ligature on the sciatic nerve by approximately 40%. 3 It is concluded that, although nervous activity is not necessary for axonal transport of transmitter granules in sympathetic neurones, intense nervous activity may accelerate the rate of granule transport.